The impact of tritium phytoremediation on plant health as measured by fluorescence. (December 2022) - Brigmon, Robin L.; McLeod, Kenneth W.; Doman, Eric; Seaman, John C.
Abstract: Phytoremediation, using plants for soil, sediment, or water contaminant clean-up, is an established technology dependent on plant health. Tritium (3H), a radioactive isotope of hydrogen that is generally found in the environment as tritiated water (HTO), is a low-level beta emitter with a half-life of 12.32 years. Chlorophyll fluorescence (CF) for monitoring risk assessment of tritium to plant health was conducted at the Tritium Irrigation Facility (TIF) located on the US Department of Energy's Savannah River Site (SRS) near Aiken, SC. Two fluorometers were evaluated in conjunction with phytoremediation at the 25 –acre TIF where tritiated groundwater is being spray–irrigated on a mixed coniferous/deciduous forested watershed as a means of reducing tritium release to a nearby stream that serves as a tributary to the Savannah River. Tritium activity in irrigated water averaged 104 + 42 pCi mL-1 during the 2003 project. Fluorescence parameters measured by the two fluorometers were well correlated with each other (p < 0.0001). Tritium in water respired from oak leaves ranged up to 1845.13 pCi ml −1 and 2138.22 pCi ml −1 in pine needles. Trees in both the test and control sites were approximately 15 years old. Here we demonstrated that fluorescence parameters provide an effective way to estimate the impact of HTO on plant health in a noninvasive, extremely rapid, and cost-effective manner. In the current study applying fluorometry, plants within the TIF phytoremediation site exposed to the site tritiated water were not significantly impacted by the tritium phytoremediation based on CF parameters as compared to the control, a nascent non-irrigated site. Highlights: Plant health was monitored at a 25 –acre Tritium Irrigation Facility (TIF) where tritiated groundwater is being spray–irrigated on a mixed coniferous/deciduous forested watershed to reduce tritium release to a nearby streams. Tritiated water irrigation had little impact on plant health as measured by fluorescence at the facility over 1 season. Tritium (pCi/ml) in water respired from oak leaves ranged up to 1845.13 pCi ml −1 and 2138.22 pCi ml −1 in pine needles. Fluorescence parameters provide an effective way to estimate the impact of radionuclides and other contaminants on plant health in a noninvasive, extremely rapid, and cost-effective manner. In this work, the, plants within the TIF phytoremediation site were in better health based on CF parameters as compared to controls, a nascent non-irrigated site.